2016
DOI: 10.1007/s10068-016-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene lactones and scopoletins from Artemisia scoparia Waldst. & Kit. and their angiotensin I-converting enzyme inhibitory activities

Abstract: Ten compounds, including a new guaiane-type sesquiterpene lactone, were isolated from the aerial parts of . The structure of the new compound was determined to be 5-hydroxyguaia-3(4),11(13),10(14)-trien-6α,12-olide, named scoparanolide. Six known sesquiterpene lactones [estafiatone, 3β,4α-dihydroxyguaia-11(13),10(14)-dien-6α,12-olide, estafiatin, preeupatundin, 3β-hydroxycostunolide, and ludovicin B] and three known coumarin derivatives (scopoletin, scoparone, and isofraxidin) were identified by nuclear magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Artemisia scoparia (AS; redstem wormwood, Asteraceae) is an edible halophyte with a unique aroma and bitter taste. Several chemical constituents, such as scopariachromane, coumarins, flavonoids, sterols, and sesquiterpene lactones, have been isolated from this plant [8,9]. Recently, various biological effects of the extracts, including antioxidant, anti-inflammatory, antipyretic, and liver protective activities, have been demonstrated [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia scoparia (AS; redstem wormwood, Asteraceae) is an edible halophyte with a unique aroma and bitter taste. Several chemical constituents, such as scopariachromane, coumarins, flavonoids, sterols, and sesquiterpene lactones, have been isolated from this plant [8,9]. Recently, various biological effects of the extracts, including antioxidant, anti-inflammatory, antipyretic, and liver protective activities, have been demonstrated [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In both DE and EE, the main compound was scoparone (DE 24.0%; EE 86.1%). Scoparone was previously isolated from A. scoparia [16][17][18][19][20][21] but was also found in some other species of this genus. Among others scoparone was found in A. capillaris, [22][23][24] A. annua, 25,26 and A. dracunculus.…”
mentioning
confidence: 99%
“…Cho and co-workers, in two separate studies on Artemisia scoparia, demonstrated the effectiveness of purified IF (1 mM) on the blockade of ACE activity (69.0%). Also IF isolated during the EtOAc and chloroform extraction of aerial parts of Artemisia scoparia, showed ACE inhibitory effects at 26.1% and 30.6%, respectively [59,136]. On the other hand, Simaratanamongkol and co-workers demonstrated the synergistic effects of IF isolated from Apium graveolens, with junipediol A on the inhibition of ACE.…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
“…Artemisia incisa Asteraceae aerial parts [56] Artemisia abrotanum Asteraceae aerial parts [57] Artemisia keiskeana Asteraceae whole plant [58] Artemisia scoparia Asteraceae aerial parts [59] Artemisia selengensis Asteraceae aerial parts [60] Impatiens balsamina Balsaminaceae root [61] Chimonanthus salicifolius Calycanthaceae aerial parts [62] Chloranthus anhuiensis Chlorantaceae whole plant [63] Chloranthus japonicus Chlorantaceae root [39] Daboecia cantabrica Ericaceae flower [21] Erica spp Ericaceae flower [21] Euphorbia lagascae Euphorbiaceae seed [64] Fraxinus exelsior Oleaceae bark [65] Fraxinus japonicus Oleaceae bark [66] Fraxinus ornus Oleaceae bark, flowers, leaves [67] Greenea corymbose Rubiaceae stem bark, leaves [43] Greenea montana Rubiaceae stem bark, root bark, leaves [43] Ixora cibdela Rubiaceae stem bark, root bark [68] Ixora javanica Rubiaceae stem bark, root bark [43] Morus alba Moraceae leaves [69] Micrandra elata Euphorbiaceae twig [70] Pelargonium reniforme Geraniaceae root [71] Peucedanum praeruptorum Apiaceae root [72] Rhododendron rubiginosum Ericaceae leaves [73] Ruyschia phylladenia Marcgraviaceae bark [29] Saposhnikovia divaricata Apiaceae root [74] Sarcandra glabra Chloranthaceae whole plant [75] Sapium discolor Euphorbiaceae stem, leaves [76] Solanum indicum Solanaceae seed [77] 2.…”
Section: Genus and Species Family Part(s)mentioning
confidence: 99%